Implementation of a* algorithm within navigation mesh in an artificial intelligence based video games - Subrando, Temmy; Prasetyatama, Fauzan Akbar; Fitrianah, Devi (International Journal of Engineering and Technology, 2018)
Pathfinding is one of the key components for Artificial Intelligence in video games, It addresses the problem to find the shortest path be-tween starting point and destination point, before A* became a staple algorithm for pathfindings, many search algorithms were used in-cluding Djikstra, Depth, and Breadth-First searches, Pathfindings are known to be resource-intensive processes especially in a large world but it mostly depends on what algorithm the game is using and what method it is implemented, using A* combined with Navigation Mesh, a popular abstract data structure in video games, this paper reviews the overall system resources used during the pathfinding pro-cess with a destination point that is always moving in a real-time so that it will gives realistic results since, in video games, a Player is constantly moves around the world, the result that we have gathered, we have concluded that A* flawlessly works with Navigation Mesh, and the performance impacts of both A* and Navigation Mesh combined is non-existent.